Peer Assessment in Facebook Comment Column about One Topic in Writing II Subject of the Fourth Semester Students of Sriwijaya University English Study Program - Inderawati, Rita; Hafiz Pratama, Ahmad; A. Loeneto, Bambang (ENGLISH FRANCA : Academic Journal of English Language and Education, 2018)
The objectives of this study were to find out (1) the completeness of the studentsâ comments on Facebook, (2) the quality of the studentsâ comments, and (3) the percentage of how well the students identified the characters of a good paragraph. The population of this study was the fourth-semester Palembang class students of English Education Study Program 2013 of Sriwijaya University. The sample of the study was 48 students that were selected by using total sampling technique. The data were collected from the studentsâ comments on Facebook of Writing II class in the academic year 2015 and analyzed by using two rubrics containing scoring systems. The results showed that the completeness in giving comments on the Facebook group could be categorized into a very good category with the final score was 10. While, the quality of the comment from the students was also Good with the final score was 15.56. The percentage of how well the students identified the characters of a good paragraph was 83.33% in very good level, 10.41 % in good level and 6.25 % in average level. Overall, the final score of the studentsâ comments from those three research questions were average with the score was 9.85. It can be concluded that the studentsâ comments on Facebook Comment Column in Writing II Class in the academic year 2015 was average. Keywords: academic writing; Facebook; peer comments